Upregulation of oxidative stress-responsive 1(OXSR1) predicts poor prognosis and promotes hepatocellular carcinoma progression. Issue 1 (1st January 2020) - Chen, Jianhui; Zhou, Jiangfan; Fu, Haotian; Ni, Xiaofeng; Shan, Yunfeng
ABSTRACT: Many studies reported that Oxidative stress-responsive 1(OXSR1) is closely related to the malignant progression of several malignancies. Nevertheless, the expression pattern and function of OXSR1 in HCC remains unknown. In present research, it was observed that the expression of OXSR1 was abnormally elevated in HCC. Upregulated OXSR1 was associated with TNM stage, and grade and was confirmed as an independent prognostic factor in HCC patients. The downregulation of OXSR1 expression effectively repressed the proliferation, migration and invasion of HCC in vivo and in vitro experiments. Western blot and qRT-PCR analysis demonstrated that mutant p53-R249S was critical for regulating the aberrant elevation of OXSR1 in HCC. Chip assay indicated that p53-R249S abrogated the binding of p53 to the OXSR1 promoter region and increased the level of POL2, H3Kac and H4Kac in the promoter region of the OXSR1, thus promoting the transcriptional expression of OXSR1. GSEA revealed that numerous cancer-related pathways were enriched in the high OXSR1 expression group. Furthermore, the expression level of OXSR1 was positively correlated with the infiltration levels of tumor infiltrating immune cells (TIICs) and PD-L1 expression in HCC by TIMER platform. In summary, our study revealed that upregulated OXSR1 was a determinant of prognosis and immune infiltration in HCC. The expression of OXSR1 was released by p53-R249S mutant, and upregulated OXSR1 in HCC promoted proliferation, migration and invasion. GraphicalAbstract: